Molecular dynamics exploration of cacophony protein interactions with brood volatiles in honey bee colonies - Haran, Ramkumar; Sumathi, Ettiappan; Sathyaseelan, Chakkarai; Jayakanthan, Mannu; Shandeep, Ganeshan; Sathiya Priya, Sundaravadivel; Kokiladevi, Eswaran; Krithika, V.P. (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Honey bee CAC proteins show varied structures and conserved domains across hymenopterans.•Phylogenetic analysis unveils hygienic behaviour evolution, aiding the understanding of bee adaptation.•Molecular interactions suggest γ-octalactone preference to CAC proteins, implying a potential role in hygienic behavior. The cacophony protein is a key component of honey bee biology that has been investigated concerning hygienic behavior. The voltage-gated calcium channel subunit α1 appears to play a significant role in modulating neuronal activity associated with the detection and response to compromised brood within honey bee colonies. Despite its essential role, the molecular mechanisms underpinning hygienic behavior remain incompletely understood. Recent research suggests that the expression of the cacophony protein is linked to the efficiency of hygienic behavior, where colonies with enhanced hygienic behavior exhibit distinct patterns of cacophony expression. Understanding the role of cacophony in honey bee behavior provides insights into the molecular mechanisms underlying social interactions within bee colonies, with implications for enhancing pollination services and mitigating threats to honey bee populations. Therefore, the present study focused on unraveling and characterizing its structure and function, using bioinformatics approaches involving sequence and phylogenetic analysis. Homology modeling developed three-dimensional models of cacophony protein for Apis cerana and A. mellifera. Molecular docking studies were performed for various brood pheromones and volatiles, triggering hygienic behavior in honey bees, against cacophony protein providing computational insights into their molecular interactions. Binding free energy calculations using MM/PBSA and MM/GBSA consistently demonstrate a higher affinity of γ-octalactone for AcerCAC protein (−21.77 ± 3.01 kcal/mol and −24.81 ± 4.07 kcal/mol respectively) compared to AmelCAC protein (−20.03 ± 3.01 kcal/mol and −21.47 ± 3.19 kcal/mol respectively). This study lays a theoretical foundation for further studies regarding the mechanism of interaction ofcacophony with hygienic behavior.